A Cross-Sectional Study of Depression, Anxiety, and Insomnia Symptoms in People in Quarantine During the COVID-19 Epidemic - Chun Lin; Xiaohong Fu (Frontiers Media S.A., 2022)
Objective: To investigate the status and influential factors of depression, anxiety, and insomnia among people in quarantine during COVID-19.Methods: Data was collected from August 2020 to November 2021 through an online survey of 1,360 people in a quarantined hotel. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Insomnia Severity Index (ISI) were used to assess different mental symptoms.Results: 19.9% (n = 270), 17.6% (n = 239) and 7.1% (n = 97) of participants had depression, anxiety and insomnia. Married (OR = 0.641, 95% CI = 0.450-0.915) was a protective factor for depression. Chronic disease (OR = 2.579, 95% CI = 1.416-4.698) was a risk factor for insomnia. No psychiatric medication history was a protective factor for depression (OR = 0.227, 95% CI = 0.068-0.757) and insomnia (OR = 0.240, 95%CI = 0.078-0.736). Female, history of mental illness, low moods at check-in, and partial/cannot understand the quarantine policies were risk factors for anxiety, depression, and insomnia.Conclusion: People in quarantine had problems with depression, anxiety, and insomnia. Female, low moods at check-in, and partial/cannot understand the quarantine policies had significant impacts. It is necessary to help quarantined people understand quarantine policies, reduce negative emotions and improve sleep quality.